MENGUNGKAP GAYA HIDUP HEDONIS PADA NOVEL TAHAJUD CINTA DI KOTA NEW YORK KARYA ARUMI EKOWATI: TINJAUAN POSKOLONIALISME - Rosfi, Suci Mardatillah; Mahmudah, Mahmudah; AJ, Andi Agussalim (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2020)
this study is to present the mindset and behavior of Indonesian people, especially hedonism as a means of fostering nationalism awareness in the era of globalization. The approach used in this research is the postcolonialism approach. The research method used is descriptive qualitative. Data was collected using documentation techniques that read and record objects to be studied. The results of the study in the form of a hedonism lifestyle became one of the characteristics of the westernized style. As for the spirit of nationalism in the form of independence, maintaining shame, mutual cooperation, unity, care will be hard to find in generations who have lost the spirit of nationalism in themselves.